2014
DOI: 10.5505/agri.2014.83788
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Single-Injection Femoral Nerve Block Provides Effective Analgesia after Total Knee Arthroplasty up to 48 Hours

Abstract: Özet Amaç: Bu çalışmanın amacı spinal anestezi ile total diz artroplastisi (TDA) yapılan hastalarda postoperatif 48 saatlik periyotta ultrason (US) kılavuzluğunda tek doz femoral sinir bloğunun (FSB) ağrı kontrolü, morfin tüketimi SummaryObjectives: The purpose of this study is to evaluate the effects of ultrasound (US) guided single-injection femoral nerve block (FNB) spinal anesthesia on pain control, morphine consumption, adverse effects, and patient satisfaction during the postoperative 48-hour period in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Urinary retention was registered in four trials [ 17 , 19 , 21 , 22 ], deep venous thrombosis (DVT) in two [ 17 , 21 ], soreness/pain in the back in two [ 18 , 23 ], hypotension in one [ 25 ], numbness around the knee in one [ 16 ], and infection around the site of injection in one [ 26 ]. No significant differences between active and control groups were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Urinary retention was registered in four trials [ 17 , 19 , 21 , 22 ], deep venous thrombosis (DVT) in two [ 17 , 21 ], soreness/pain in the back in two [ 18 , 23 ], hypotension in one [ 25 ], numbness around the knee in one [ 16 ], and infection around the site of injection in one [ 26 ]. No significant differences between active and control groups were reported.…”
Section: Resultsmentioning
confidence: 99%
“…There are a limited number of studies regarding FNB use in TKA in our country. Sahin et al [ 15 ] performed US-guided FNB using 40 mL of 0.5% bupivacaine after T12 regression of spinal anesthesia. Their study reported significant decrease in opioid consumption with sufficient and effective analgesia for up to 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have evaluated the effectiveness of FNB or have compared it with another analgesia method in TKA. A large majority of these studies have reported the use of 0.25% bupivacaine for single dose FNB [ 3 , 8 , 15 , 23 , 24 ]. When the catheter was placed near the femoral nerve, bolus of 0.25% bupivacaine was followed by 0.125% concentration as a continuous infusion [ 20 , 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 The lateral femoral cutaneous nerve is involved in innervation to the lateral knee skin and in pain syndrome 17 , 21 , 22 following TKA, and this nerve should be blocked along with the other three nerves. This study compared the efficacy of ultrasound (US)-guided preoperative femoral nerve block (FNB) alone 1 6 to that of US-guided multiple preoperative nerve block (MNB) of all four nerves (femoral, sciatic, obturator, and lateral femoral cutaneous), since, to the best of our knowledge, such a comparison has not yet been performed or published.…”
Section: Introductionmentioning
confidence: 99%